PENGARUH KETERSEDIAAN RUANG TERBUKA HIJAU TERHADAP IKLIM MIKRO DI KABUPATEN KUNINGAN - Sudrajat, Fizar Ali; Nasihin, Iing; Nurlaila, Ai (Fakultas Kehutanan dan Lingkungan, Universitas Kuningan, 2024)
Green open space (GOS) is an essential component of urban open space. This RTH is planted with a variety of vegetation to support the direct or indirect benefits generated by GOS in the city, namely safety, comfort, welfare, and the aesthetic appeal of the urban area. Trees that grow in green spaces have the ability to transpire, absorb solar radiation, and provide shade, thereby influencing the surrounding environment. Green spaces in Kuningan Regency have a significant role in microclimate control. This study aims to determine the effect of green spaces on microclimate using direct data measurements with three parameters: air temperature, air humidity, and light intensity. The data is then processed into variable data and analyzed using the Pearson correlation method with the help of SPSS software. The results indicate that the relationship between green spaces and microclimates exhibits distinct characteristics. Specifically, the correlation between green spaces and air temperature is found to be strong, that between green spaces and air humidity is moderate, and that between green spaces and light intensity is weak.Keywords: green open space, microclimate, Kuningan Regency.